1,4-Bis(methylsulfanyl)naphthalene - Çelik, Ísmail (International Union of Crystallography, 2009)
The molecule of the title compound, C(12)H(12)S(2), is close to planar, with the methyl C atoms deviating by 0.019 (1) and 0.221 (2) Å from the naphthalene mean plane. In the crystal structure, the shortest S⋯S contact of 3.6864 (9) Å is longer than the van der Waals contact distance.